2023
DOI: 10.1007/s10914-022-09647-z
|View full text |Cite|
|
Sign up to set email alerts
|

The vocal apparatus: An understudied tool to reconstruct the evolutionary history of echolocation in bats?

Abstract: Laryngeal echolocation in bats could have evolved following two scenarios: a single origin from a common ancestor or an independent acquisition inside the two clades Yinpterochiroptera and Yangochiroptera. Later, some members of Yinpterochiroptera possibly lost their ability to echolocate. In bats, the larynx produces vocalizations for communication and, in most species, for echolocation. Here, we describe how comparative chiropteran laryngeal morphology is a novel area of research that could improve the under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 98 publications
1
10
0
Order By: Relevance
“…Characteristics ( 2), (3), and ( 5) are consistent with the descriptions of Rhinolophus hipposideros [43] and Hipposideros caffer [26]. As reported in other laryngeally echolocating bats [19,49], the intrinsic laryngeal muscles of horseshoe bats are hypertrophied compared to those of mice, and the laryngeal cartilage is drastically modified to provide attachment sites for these muscles. The overall pattern of innervation of the intrinsic laryngeal muscles of horseshoe bats was identical to that of mice, except for a novel branch of the cranial laryngeal nerve and the absence of the foramen thyroideum (Fig.…”
Section: General Morphology Of the Hyolaryngeal Complex In The Horses...supporting
confidence: 85%
See 2 more Smart Citations
“…Characteristics ( 2), (3), and ( 5) are consistent with the descriptions of Rhinolophus hipposideros [43] and Hipposideros caffer [26]. As reported in other laryngeally echolocating bats [19,49], the intrinsic laryngeal muscles of horseshoe bats are hypertrophied compared to those of mice, and the laryngeal cartilage is drastically modified to provide attachment sites for these muscles. The overall pattern of innervation of the intrinsic laryngeal muscles of horseshoe bats was identical to that of mice, except for a novel branch of the cranial laryngeal nerve and the absence of the foramen thyroideum (Fig.…”
Section: General Morphology Of the Hyolaryngeal Complex In The Horses...supporting
confidence: 85%
“…Abduction of the glottis to vibrate the vocal fold involves contraction of the dorsal cricoarytenoid muscle. It has been suggested that tracheal chambers contribute to sound intensity [26,27,49,72]. Given that the ventral part of the cricothyroid muscle is attached to the lateral tracheal chambers, mineralization of the tracheal chambers can be promoted by superfast contraction of this muscle.…”
Section: Relationship Between Development and Pulse Ontogenymentioning
confidence: 99%
See 1 more Smart Citation
“…Our work established foundation for further studies of bat larynx to reveal not only bat laryngeal echolocation origin but also their unique evolutionary history. In the future, functional morphological analyses should be done to understand the relationship between laryngeal anatomy and acoustic properties of the ultrasonic sounds produced in bats [30]. Moreover, new insights into evolutionary history of the bat laryngeal echolocation should be obtained from observation of innervation pattern of the laryngeal muscles [30,37] and studies of molecular mechanisms that regulate the laryngeal morphogenesis and SFM formation in the echolocating bat lineages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the cricothyroid muscle, whose contraction produces high-frequency sound in mammals (figure 1b and electronic supplementary material, figure S1), is enlarged and specialized into superfast muscle (SFM) in yangochiropteran bats, allowing them to emit several dozens of ultrasonic pulses per second [27][28][29]. Morphological and molecular comparisons of the larynx between echolocating and non-echolocating linages, and within echolocating linages, may shed light on the origin of chiropteran laryngeal echolocation [30].…”
Section: Introductionmentioning
confidence: 99%